Scar Assessment Tools: How Do They Compare? - Choo, Amanda Min Hui; Ong, Yee Siang; Issa, Fadi (Frontiers in Surgery, 2021)
Healing after dermal injury is a complex but imperfect process that results in a wide range of visible scars. The degree of disfigurement is not the sole determinant of a scar’s effect on patient wellbeing, with a number of other factors being critical to outcome. These include cosmetic appearance, symptoms such as itch and pain, functional loss, psychological or social problems and quality of life. An accurate assessment of these domains can help clinicians measure outcomes, develop and evaluate treatment strategies. A PubMed literature search was performed up to 31st March 2020. Ten objective scar measurements, four Clinician-Reported Outcome Measures (CROMs), six Patient-Reported Outcome Measures (PROMs) and one combined measure were evaluated for their reliability, clinical relevance, responsiveness to clinical change and feasibility. Many quantitative tools were limited in their clinical relevance and feasibility, whereas few qualitative CROMs and PROMs have undergone rigorous assessment. This review examines currently available assessment tools, focusing primarily on subjective scar measurements (CROMs, PROMs), and offers a perspective on future directions in the field.